Ambientes computacionais no contexto da geometria: panorama das teses e dissertações do Programa de Educação Matemática da PUC-SP de 1994 a 2007 - Rosa, Kelly Cristina (2009)
This study aims to present an overview work on the Mathematics Education thesis and dissertations at Pontifícia Universidade Católica de São Paulo from 1994 to 2007. These dissertations and theses were related to computational environment as tools in the Geometry context therefore, they were able to help this research to identify the most used tendencies on the subject matter so that the current studies can have a funded base of information where they can keep on going the new researches. The study analysis source is composed by thirty-two (32) selected pieces of work searched by titles, abstracts and key-words. The State of Art was the methodology process base. An outline of each work was elaborated based on the 10 activities by Romberg (1992). The study results show that six (06) Math objects were preferred, nine (09) where the computational environment were used and twenty-seven (27) where the author have chosen Cabri. Among the categorized Math objects, we could notice that fifteen (15) of them were related to the Geometric Transformations